Musika a videodocumentary on the American colonial and contemporary traditions in Philippine music - Cultural Center of the Philippines (Manila The Center, 1993)
Shows the American colonial influences on 20th century music in the Philippines.
VHS.
Narration, Eddie Mercado ; producers, Rowena E. Concepcion, Libertine C. Santos.
Keywords: Santos, Ramon P; Music -- History. -- Philippines; Music -- American influences. -- Philippines; Documentary